Legal Reform In Handling Inmates With Mental Health Disorders In Correctional Institutions - Tiur Hasmida Hutagalung; Suparno (al-Battar: Jurnal Pamungkas Hukum, 2025)
The treatment of inmates with mental health disorders remains a persistent challenge within the Indonesian correctional system. Although Law No. 22 of 2022 on Corrections, Law No. 18 of 2014 on Mental Health, and several implementing regulations recognize prisoners’ rights to healthcare, they fail to provide explicit mechanisms for the identification, treatment, and rehabilitation of inmates with mental health disorders. This study aims to analyze the extent to which existing legal frameworks accommodate the specific needs of inmates with mental health disorders and to identify legal gaps that hinder the effective protection of their rights. Employing a normative juridical research method with statutory, conceptual, and comparative approaches, this study examines relevant legislation and compares Indonesia’s regulatory framework with practices adopted in several other jurisdictions. The findings reveal a significant legal vacuum characterized by the absence of standardized procedures for early identification, inadequate mental health services within correctional institutions, and weak coordination between correctional and health authorities. This condition increases the risk of human rights violations, institutional violence, ineffective rehabilitation, and failed social reintegration. The study concludes that comprehensive legal reform is urgently required to establish clear regulatory standards, strengthen institutional capacity, and integrate a rehabilitation-oriented, health-based approach within the correctional system. Such reforms are essential to ensure the protection of inmates’ rights and to realize a humane and effective correctional framework.